The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00125-002-0997-0
|View full text |Cite
|
Sign up to set email alerts
|

Protection of rat pancreatic islets by potassium channel openers against alloxan, sodium nitroprusside and interleukin-1β mediated suppression—possible involvement of the mitochondrial membrane potential

Abstract: Aims/hypothesis. We aimed to study the effects of two K ATP channel openers (KCO), diazoxide and the more potent compound NNC 55-0118, on beta-cell suppression and/or toxicity induced by alloxan, sodium nitroprusside and IL-1β. Methods. Islets from rats were exposed to 0.3 mmol/l diazoxide or NNC 55-0118 for 30 min and either alloxan (0.5 mmol/l), sodium nitroprusside (0.5 mmol/l) or IL-1β (12.5 or 25 U/ml) were added and the incubation continued for 30 min. Islets were then washed and incubated for 24 h befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Diazoxide enhances ischemic preconditioning in the heart (12) and neurons (13,14) through a mitochondrial interaction that may be coupled to reduction of mitochondrial reactive oxygen species production (14). In ␤-cells diazoxide decreases mitochondrial membrane potential in acute experiments (15,16) and may inhibit succinate oxidation (17). We did not observe any effect on gene expression for succinate dehydrogenase, represented in the array by four genes encoding for separate subunits.…”
Section: Discussionmentioning
confidence: 72%
“…Diazoxide enhances ischemic preconditioning in the heart (12) and neurons (13,14) through a mitochondrial interaction that may be coupled to reduction of mitochondrial reactive oxygen species production (14). In ␤-cells diazoxide decreases mitochondrial membrane potential in acute experiments (15,16) and may inhibit succinate oxidation (17). We did not observe any effect on gene expression for succinate dehydrogenase, represented in the array by four genes encoding for separate subunits.…”
Section: Discussionmentioning
confidence: 72%
“…Overall, these results suggested that diazoxide might be exerting effects independent of the activation of plasma membrane K ATP channels that are responsible for the potentiation of glucose-stimulated DNA synthesis. Findings by Kullin et al (31) also reported that K ATP channel openers including diazoxide decreased the vulnerability of rat islets to free radicals induced by alloxan, nitroprusside, or IL-1␤. It was proposed that K ATP channel openers by their ability to decrease Ca 2ϩ influx due to ␤-cell membrane hyperpolarization in combination with their direct effect to decrease the mitochondrial membrane potential reduced ATP production necessary for the activation of apoptotic pathways.…”
Section: Tablementioning
confidence: 87%
“…Recent reports have shown that K ATP channel activation using diazoxide or other selective openers induces ␤-cell rest and protection against the effects of high-fat diet (40)(41)(42). Chronic studies where HCN channel function or expression is manipulated are required to determine the potential roles of these channels on ␤-cell function.…”
Section: Discussionmentioning
confidence: 98%